Photosynthetic traits as indicators for phenotyping urban and peri-urban forests: A case study in the metropolitan city of Rome. (August 2019) - Fusaro, Lina; Salvatori, Elisabetta; Mereu, Simone; Manes, Fausto
Highlights: Functional traits of photosynthetic machinery used for phenotyping urban forests. FRI740/800 is well related to general functionality of photosynthetic machinery. PRI is correlated to ChlF parameters connected to dark phase of photosynthesis. Down regulation of PSII is the main strategy to cope with stress in urban forest. Multi-traits approach as a mean to assess the vitality of UF at large spatial scale. Abstract: Phenotyping for functional traits associated with photosynthetic machinery could be a promising approach for studying the performance of green infrastructures in metropolitan areas. Trait-based indicators hold important information about ecosystem processes and how environmental constrains may influence the provisioning of services. This work aims to apply a high-throughput phenotyping approach to an urban and a peri-urban forest, in order to evaluate the functionality of vegetation through direct measures of photosynthetic traits such as spectroscopy indices, chlorophyll a fluorescence (ChlF) and leaf chemistry (nitrogen and carbon content). Quercus ilex L. was chosen as the target species for its wide distribution in natural and urban greening, sampled at two distances from a high traffic road (urban forest) and in a natural preserved area (peri-urban forest). The reflectance index most related to the general functionality of photosynthetic machinery was the Fluorescence Ratio Indices FRI740/800, whereas the highest informative indicator traits to differentiate the functionality of Q. ilex in different periods of the year in the urban and peri-urban forest were Normalized Difference Vegetation Index (NDVI), Structure-Insensitive Pigment Index (SIPI) and Normalized Difference Nitrogen Index (NDNI). Interestingly, Photochemical Reflectance Index (PRI) was not only correlated to functional parameters connected to PSII light absorption side, but also with ChlF parameters related to carbon assimilation such as regeneration capacity of the end acceptors. ChlF parameters are effective indicators for highlighting differences between sites, pointing out that the urban forest sites have lower functionality compared to peri-urban one.